The Quality of Information and Related Sources of Information as an Assumption for Effective Decision-Making Process for Tourists to Travel in the European Tourism Market - MihajloviÄ‡, Iris; ÄŒoloviÄ‡, Zorica KrÅ¾elj (Mediterranean Journal of Social Sciences, 2012)
Assumption of effective decision-making process for tourists on a trip is based on quality information. In order to gain insight ofthe source of information about tourists' decisions related to travel and to the European tourist market, a secondary research wasconducted. Subjects-tourists, who participated in the survey, were asked to indicate which sources of information they use when makingdecisions about travel plans, by valuing different sources of information as very important to less important ones. Survey results indicatehighly prevailing sources of information such as "recommendations of friends and colleagues," and the Internet as a new technologicalsolution tourists use when making decisions about their travel resort. The most important sources of information, according to thedemographic characteristics of respondents in all 27 EU Member States, were also analyzed. In this paper, preliminary results arebrought in connection with the timeframe and poor economic condition determining the behavior of consumers and their capabilitiesrelated to travel, and hence the frequency of travel, tourism trends and alternative travel destinations which are a result of mostacceptable solutions to these conditions. Classical sources of information, such as travel agencies with the exception of "therecommendations of friends and colleagues", have new challenges and additional responsibilities on how to effectively implement statedtechnological solutions into new business processes.